2013
DOI: 10.1111/jgh.12110
|View full text |Cite
|
Sign up to set email alerts
|

IL28B genotype is not useful for predicting treatment outcome in Asian chronic hepatitis B patients treated with pegylated interferon‐α

Abstract: In the context of a small possible effect size and high frequency in Asian populations, IL28B genotyping is likely to have, at best, limited clinical utility for predicting peg-IFN treatment outcome for CHB patients in the Asia-Pacific region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…Other previous studies tried to determine whether having favourable IL28B genotype markers is associated with a better response to interferon therapy in HBeAg-negative adult patients, but the results were inconclusive. Some reports have suggested that the presence of favourable IL28B genotypes is associated with a better response to treatment[31,37], while others have indicated that there is no association between IL28B SNPs and the response to treatment with interferon[26,38]. In the present study, we demonstrated a statistically significant relationship between the rs12979860 marker and the response to treatment with interferon in patients with CHB.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Other previous studies tried to determine whether having favourable IL28B genotype markers is associated with a better response to interferon therapy in HBeAg-negative adult patients, but the results were inconclusive. Some reports have suggested that the presence of favourable IL28B genotypes is associated with a better response to treatment[31,37], while others have indicated that there is no association between IL28B SNPs and the response to treatment with interferon[26,38]. In the present study, we demonstrated a statistically significant relationship between the rs12979860 marker and the response to treatment with interferon in patients with CHB.…”
Section: Discussionsupporting
confidence: 55%
“…To evaluate the therapeutic effects, we assessed virological, serological and biochemical responses by analysing HBV DNA levels, HBsAg status and ALT activity before, during and 24 wk after the end of therapy. A limit of 2000 IU HBV DNA/mL, which has been used in the literature, was adopted in the virological response analysis[26]. In our study, we determined the impact of genetic markers on the efficacy of therapy by comparing patients in terms of achieving a defined therapeutic response.…”
Section: Methodsmentioning
confidence: 99%
“…Holmes et al . retrospectively analysed the role of IFN‐λ3 rs12979860 in 96 Australian patients (62% HBeAg‐positive) treated with 48 weeks of PegIFN and followed up for 39 months . The majority of the patients (84%) carried CC genotype, whereas 15% and 1% carried CT and TT genotype, respectively, with similar frequency of CC genotype according to HBeAg status (85% and 83%).…”
Section: Host Genetics and Response To Ifn Therapymentioning
confidence: 99%
“…A report published by Holmes et al (2013) showed that IL28B genotype (rs12979860) is not a useful predicting marker for treatment outcome in Asian chronic hepatitis B patients treated with pegylated interferon-α. The study includes very small number of patients as well control subjects.…”
Section: Dear Editormentioning
confidence: 99%